Diapause in Amblyseius andersoni Chant (=A. potentillae Garman) (Acarina Phytoseiidae) in the climate of the Po Valley (Bollettino di zoologia agraria e bachicoltura, 2024)
Overwintering Amblyseius andersoni females were collected from peach trees in different periods of winter and were kept in the laboratory with a photoperiod of 8 hours, a temperature of 20 °C and 80-90% RH, with the aim of finding out whether these females enter diapause. The results were as follows:1) There is imaginal reproductive diapause in 100% of the A. andersoni females during the month of November, this percentage decreasing gradually up to Febraury.2) In a natural environment at the beginning of winter the immature forms and males disappear, and only the females in diapause survive.3) After the first ten days of January some of the females are able to oviposit and are prevented from oviposition only by the low temperature; this condition continues for about three months (up to the last ten days of Aprii) in a natural environment.4) Keeping the overwintering females totally without food at a temperature of 20 °C and 80-90% RH revealed a resistance to hunger that is greater among the females in diapause, but is considerable even after diapause. This is therefore to be considered a valid character of this species.5) Diapause is induced by ecological conditions (duration of daylight and scotophase temperature) which in the Po Valley climate obtain in the last ten days of August and the first ten days of September; the females in diapause therefore come from eggs laid during this period.The caracteristics and nature of diapause are then discussed.
Keywords: diapause; Amblyseius andersoni; photoperiod; Po Valley